Evaluation of nutritional status of infants in rural areas of Bindura - Machengete, Vongai Praise (BUSE, 2020)
Stunting is a form of malnutrition that is common among children below the age of 5 years and it can only be prevented below the age of 2 years. In Bindura District stunting levels have been on the rise and government and other implementing partners have been trying food mitigation programs to curb this challenge but stunting is still prevalent. The above stated challenge prompted the researcher to make an analysis of nutritional status of children aged 6 to 23 months in Bindura District. A total of 153 households with children between 6 to 23 months were sampled. The primary data were obtained through the use of a survey questionnaire with closed and open-ended questions, while the secondary data was extracted from journals, newspapers and library sources. To assess nutrition status of infants the researcher collected anthropometric measurements revealing 22.9% of the infants were moderately stunted and 1.3% were severely stunted. Multiple linear regression was used to determine the factors that affect nutrition status of infants. The outcome of linear regression showed that gender of household head, age of household head, household size, source of income, food assistance, number of meals eaten per day, decline in level of access to food compared to previous income spent on food, and problems faced, significantly affect nutrition status positively (P<0.05). The regression results also revealed that coping strategies positively affect nutrition status (P<0.05). The majority of the caregivers resorted to limiting the number of meals, eating less preferred food, limiting portion of meal and restricting adult food consumption as infant food insecurity coping mechanisms. The government is recommended to design intervention strategies that prevent the current cases of moderate stunting to worsen. A move that incorporate Ministry of Health and Child Care. Keywords: malnutrition, stunting, wasting, nutrition status, coping strategies.
Keywords: Malnutrition; Nutrition status